Fostering Stress Resilience Among Business Students: The Role of Stress Mindset and Self-Connection. Issue 4 (August 2021) - Klussman, Kristine; Lindeman, Meghan I. Huntoon; Nichols, Austin Lee; Langer, Julia
Educators are becoming increasingly concerned about the high rates of burnout among their students. Although the solution may appear to be reducing the stress their students experience, simply reducing stress is a temporary solution and does not help students when they enter the workforce and encounter increased stressors. A better option may be to consider the ways in which students can increase stress resilience in ways that will help them long after they leave the classroom. With this idea in mind, we tested for relationships between two individual difference variables, stress mindset and self-connection, and burnout and life satisfaction among business students. The results showed there was a positive relationship between viewing stress as debilitating and prevalence of both personal and school-related burnout. Additionally, self-connection was negatively related to personal burnout and greater life satisfaction. Stress mindset and self-connection also interacted to predict both personal and school burnout. The results suggest that promoting adaptive views of stress and becoming more self-connected may lead to a better student experience.